2008
DOI: 10.17221/349-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effects of space allowance on egg yield, egg quality and plumage condition of laying hens in battery cages

Abstract: This study was conducted to investigate the effects of cage stocking density on egg yield, some egg quality traits and plumage condition in laying hens. Eighteen weeks-old 264 ISA-Brown pullets were divided into four cage density groups. The densities were 2 000, 1 000, 667 and 500 cm 2 per hen (by allocating 1, 2, 3 and 4 hens per cage; floor area 40 × 50 cm) with 48, 30, 24 and 21 replicate cages, totally 123 three-tier battery cages. During the experimental period from 18 to 53 weeks of age, all birds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 40 publications
8
36
1
8
Order By: Relevance
“…Also, Gharib (2006) displayed that increasing bird density resulted in a significant negative effect on yolk color scores compared to birds stocked at lower cage density, however housing birds at low cage density improved egg quality. On the other hand, Sarica et al, (2008) reported that increasing cage density in chickens to 5 bird/cage reflected no affect on egg shell quality and egg weight. Carcass characteristics: Data of carcass characteristics of laying Japanese quail at 21 weeks of age as a percentage of live body weight are given in Table ( 6).…”
Section: Hormonal Assays and Immunological Responsementioning
confidence: 97%
“…Also, Gharib (2006) displayed that increasing bird density resulted in a significant negative effect on yolk color scores compared to birds stocked at lower cage density, however housing birds at low cage density improved egg quality. On the other hand, Sarica et al, (2008) reported that increasing cage density in chickens to 5 bird/cage reflected no affect on egg shell quality and egg weight. Carcass characteristics: Data of carcass characteristics of laying Japanese quail at 21 weeks of age as a percentage of live body weight are given in Table ( 6).…”
Section: Hormonal Assays and Immunological Responsementioning
confidence: 97%
“…Published reports of the influence of highdensity caging on oviduct health and function are lacking. Sarica et al (2008) showed that higher density rearing decreased egg production, egg mass, and other performance indicators of hens, and that increasing the space per hen significantly enhanced egg production. Thus, we hypothesized that stocking density or rearing pattern may affect oviduct health and function in hens.…”
Section: Introductionmentioning
confidence: 99%
“…Optimum livability was achieved at 451 cm 2 /hen (70 in 2 /hen; Garner et al, 2011). Numerous controlled studies (e.g., Adams and Craig, 1985;Anderson et al, 2004;Jalal et al, 2006;Sarica et al, 2008) have shown that when hens in conventional cages are crowded, they lay fewer eggs and experience higher mortality. The contradictory results of the current study, showing that crowding (cage floor space <400 cm 2 or 62 in 2 /hen) did result in higher mortality but unexpectedly also resulted in higher hen-housed egg production, might be explained if most mortality in crowded cages occurred late in the production cycle, whereas mortality in more spacious cages occurred earlier in the production cycle, as might be the case with cannibalism.…”
Section: Floor Spacementioning
confidence: 99%
“…Thus, the hens appeared to reallocate energy to producing fewer larger eggs when given more space. Existing literature on the effect of stocking density on case weight of eggs is inconsistent (Du Plessis and Erasmus, 1972;Davami et al, 1987;Brake and Peebles, 1992;Zeidler, 2002;Onbasilar and Aksoy, 2005;Jalal et al, 2006;Sarica et al, 2008). These inconsistencies could be attributed to a multitude of factors, including but not limited to genotypic and dietary differences and confounding effects of feeder and drinker space with stocking density.…”
Section: Floor Spacementioning
confidence: 99%